Investigation of concrete recycling in the U.S. construction industry - Jin, Ruoyu; Cheng, Qian (Elsevier, 2015)
The emerging sustainable development movement in the construction industry requires the recycling of waste materials to reduce the negative environmental impact of construction activities. In many countries, old concrete, a major waste stream generated from the demolition of obsolete buildings/structures, is being recycled. However, for various reasons, progress toward concrete recycling varies from country to country. This paper discusses the current status of concrete recycling in the U.S. construction industry based on results from a two-part questionnaire survey. The first part of the survey collects information on the recycling practices of surveyed concrete companies. The second part adapts questions from a study conducted in Australia and Japan to examine the awareness, benefits, difficulties, and recommended methods related to concrete recycling. The findings showed that although recycling old concrete is common in the U.S., its application is mostly limited to backfill and pavement base; using waste concrete in new concrete production is not widely applied. There are also similarities and differences in the perceptions of concrete recycling between U.S. concrete companies and their counterparts in Australia and Japan.